2023
DOI: 10.1017/s1366728923000755
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and cued language switching in late bilingual speakers

Saskia Mooijman,
Rob Schoonen,
Marina B. Ruiter
et al.

Abstract: Previous research examining the factors that determine language choice and voluntary switching mainly involved early bilinguals. Here, using picture naming, we investigated language choice and switching in late Dutch–English bilinguals. We found that naming was overall slower in cued than in voluntary switching, but switch costs occurred in both types of switching. The magnitude of switch costs differed depending on the task and language, and was moderated by L2 proficiency. Self-rated rather than objectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
1
0
0
Order By: Relevance
“…In order to yield an approximate 50% switching rate in the free-naming condition, participants were instructed to "try to use two languages equally often and in a random order" (Arrington & Logan, 2004;Zhang et al, 2015). A switching rate of 46% was observed in the present study, similar to studies on unbalanced bilinguals ( de Bruin & Xu, 2023;Liu et al, 2019;Mooijman et al, 2023;Sánchez et al, 2022) but higher as compared to studies examining free language switching in balanced bilinguals (Blanco-Elorrieta & Pylkkänen, 2017; de Bruin et al, 2018de Bruin et al, , 2020Grunden et al, 2020;Jevtović et al, 2020). Interestingly, Gollan and Ferreira (2009) showed that when the instructions of free picture-naming is to use "whatever language comes to mind", bilinguals switch less often than when the instruction is "using each language about half the time" for the same task, indicating that the specific instruction plays a critical role in how frequent bilingual participants switch between languages in a free-naming task.…”
Section: Discussionsupporting
confidence: 74%
“…In order to yield an approximate 50% switching rate in the free-naming condition, participants were instructed to "try to use two languages equally often and in a random order" (Arrington & Logan, 2004;Zhang et al, 2015). A switching rate of 46% was observed in the present study, similar to studies on unbalanced bilinguals ( de Bruin & Xu, 2023;Liu et al, 2019;Mooijman et al, 2023;Sánchez et al, 2022) but higher as compared to studies examining free language switching in balanced bilinguals (Blanco-Elorrieta & Pylkkänen, 2017; de Bruin et al, 2018de Bruin et al, , 2020Grunden et al, 2020;Jevtović et al, 2020). Interestingly, Gollan and Ferreira (2009) showed that when the instructions of free picture-naming is to use "whatever language comes to mind", bilinguals switch less often than when the instruction is "using each language about half the time" for the same task, indicating that the specific instruction plays a critical role in how frequent bilingual participants switch between languages in a free-naming task.…”
Section: Discussionsupporting
confidence: 74%